Obstacles to implementing initiatives of social responsibility in small and medium-size firms - Česynienė, Rima; Neverkevič, Marina (Business, Management and Economics Engineering, 2010)
The purpose of the paper is to analyse the obstacles to implementing social responsibility initiatives in small and medium-size business firms. The implementing fields and the importance of corporate social responsibility (CSR) initiatives in small and medium-size business firms are stressed in the paper. The current situation of CSR in Lithuanian small and medium-size firms is presented. The research data allowed discovering that the main obstacle to implement social responsibility in the small and medium-size firms is the managers’ attitude that social responsibility is a matter of great concern only to large companies. 43% of respondents indicated this obstacle. On the other hand, the research data allowed finding out that in our turbulent environment social responsibility in small and medium-size business firms is not a random phenomenon (71%), and it is constant concern to managers, which provides for the budget (54%). The understanding that social responsibility initiatives are only charity or philanthropy is also declined, only 5% of the respondents think so, however, 32% of firms are supporting charitable initiatives. The most stimulating factors in the implementation of CSR are: staff loyalty and job satisfaction, a better image of the company, long-term competitiveness of the business advantage, the increased consumers requirements. Socially responsible behaviour disincentives are: the lack of human resources (51%), lack of information about gain from socially responsible activities (50%), lack of financial resources (28%). Both theory and practice agree that the implementation of CSR issues is most dependent on the leader’s attitude. The managers of small and medium-size business firms mostly are coordinating the implementation of CSR initiatives (70% of respondents). The results of the empirical research of CSR initiatives implementation in business prac-tices were presented in the possible model of tools which stimulates social responsibility initiatives in small and medium-size business firms. This integrated model includes pu-blic, government and business efforts and interests: 1) improvement of public policy, 2) revitalization of public organizations; 3) encourage and support research, 4) integration of CSR into education, 5) singleness of purpose (depending on companies’ specifics), 6) increase of managers’ consciousness, 7) implementation of a step-by-step approach. Article in Lithuanian. Įmonių socialinė atsakomybė ir jos iniciatyvų diegimo kliūtys smulkiojo ir vidutinio verslo įmonėse